Privacy Principles in Malay House Design: Integrating Visual and Acoustic Privacy in Selatpanjang Residences - Samra Boby; Aulia Dwira Nirfalini; Lindarto Dwi; Fachrudin Hilma Tamiami (E3S Web of Conferences)
The House of Malay Selatpanjang (RMS) in Riau, Indonesia, integrates traditional Malay architectural design and Islamic environmental principles into the privacy of the built environment. This research aims to understand the visual and acoustic privacy of RMS compared to the principles enlisted in the book “Traditional Islamic Principles of Built Environment.” It involves detailed observations, spatial measurements, and in-depth interviews of the occupants about how privacy is maintained in their daily activities and what it means. The findings show that RMS successfully incorporates the guidelines given by Islamic privacy through the strategic placement of doors, windows, and partitions. While visual privacy is assured through window and door design that is restricted from allowing views or approaches from without, acoustic privacy is achieved using physical dividers and cultural norms that require talking at low volume while within the house. These measures translate to distinctive public, semipublic, and private zones within the home, thus affording proper interaction while respecting personal space. This study is beneficial as it provides critical insight into how Islamic architectural principles could be translated into the practical set-up of modern residential design. The study gives valuable recommendations for architects and designers who want to make culturally and religiously sensitive housing solutions by showing how traditional values can be retained and brought into contemporary living environments. Implications go beyond the local context, pointing out a model of sustainable and respectful residential design that honors cultural heritage and modern needs.